Peran Kualitas Layanan Elektronik, Presepsi Kemudahan, dan Kualitas Informasi terhadap Niat Pembelian Online Streaming Musik Spotify - Samudro, Dicky Anugrah; Widyastuti, Widyastuti (Jurnal Ilmu Manajemen, 2020)
This study aims to the determinant effect of e-service quality, perceived ease of use, and information quality toward online purchase intention to paid digital streaming music Spotify. This research uses quantitative data. The sampling technique used is non-probability sampling with the type of judgmental sampling. In this study, the respondent is free service users streaming music Spotify access with smartphone, the sample used was 220 respondents. Data is processed using multiple linear regression. The results of this study indicate that e-service quality significantly affects online purchase intention, perceived ease of use significant effect on online purchase intention, and information quality significant effect toward online purchase intention.